المقارنة بين طريقة الإيحائية و طريقة المغناتيسي في تعليم اللغة العربية - Qiya Khaira Hikmatillah (Universitas Yudharta Pasuruan, 2020)
This study is a comparison of the suggestopedia method and the hypnoteaching method. Sugestopedia is a method that has been initiated for a long time, while hypnoteaching is a method of updating. This research was conducted to determine the advantages and disadvantages of both, so that the updating of the method with the hypnoteaching method can provide learning convenience for students. The method used in this research is descriptive qualitative analysis. The main data sources from this study are the books related to suggestion supported articles and magazines that are in line with the research topic. Therefore this article will explore where the suggestopedia is. In addition to suggestopedia, there is also a hypnoteaching method that uses suggestions and motivation so that students can receive lessons well. Then what is the difference between the two methods. Both of these methods have differences in terms of implementation, but the time required is still the same, which requires a long process to be able to provide suggestions and enjoyment while learning. From a long process and a series of techniques from these two methods it can be seen that these two learning methods are not at all suitable for students who need to learn in a short time, but with a class with a few students, their ability and achievement will be more monitored.